Decipher test impacts decision making among patients considering adjuvant and salvage treatment after radical prostatectomy: Interim results from the Multicenter Prospective PRO‐IMPACT study. Issue 15 (19th April 2017) - Gore, John L.; du Plessis, Marguerite; Santiago‐Jiménez, María; Yousefi, Kasra; Thompson, Darby J. S.; Karsh, Lawrence; Lane, Brian R.; Franks, Michael; Chen, David Y. T.; Bandyk, Mark; Bianco, Fernando J.; Brown, Gordon; et al.
Abstract : BACKGROUND: Patients with prostate cancer and their providers face uncertainty as they consider adjuvant radiotherapy (ART) or salvage radiotherapy (SRT) after undergoing radical prostatectomy. The authors prospectively evaluated the impact of the Decipher test, which predicts metastasis risk after radical prostatectomy, on decision making for ART and SRT. METHODS: A total of 150 patients who were considering ART and 115 who were considering SRT were enrolled. Providers submitted a management recommendation before processing the Decipher test and again at the time of receipt of the test results. Patients completed validated surveys on prostate cancer (PCa)‐specific decisional effectiveness and PCa‐related anxiety. RESULTS: Before the Decipher test, observation was recommended for 89% of patients considering ART and 58% of patients considering SRT. After Decipher testing, 18% (95% confidence interval [95% CI], 12%‐25%) of treatment recommendations changed in the ART arm, including 31% among high‐risk patients; and 32% (95% CI, 24%‐42%) of management recommendations changed in the salvage arm, including 56% among high‐risk patients. Decisional Conflict Scale (DCS) scores were better after viewing Decipher test results (ART arm: median DCS before Decipher, 25 and after Decipher, 19 [ P <.001]; SRT arm: median DCS before Decipher, 27 and after Decipher, 23 [ P <.001]). PCa‐specific anxiety changed after Decipher testing; fear of PCa disease recurrence in the ART arm ( P = .02) and PCa‐specific anxiety in the SRT arm ( P = .05) decreased significantly among low‐risk patients. Decipher results reported per 5% increase in 5‐year metastasis probability were associated with the decision to pursue ART (odds ratio, 1.48; 95% CI, 1.19‐1.85) and SRT (odds ratio, 1.41; 95% CI, 1.09‐1.81) in multivariable logistic regression analysis. CONCLUSIONS: Knowledge of Decipher test results was associated with treatment decision making and improved decisional effectiveness among men with PCa who were considering ART and SRT. Cancer 2017;123:2850–59. © 2017 American Cancer Society . Abstract : Use of the Decipher test appears to result in a change in treatment decision making in a substantial percentage of men with prostate cancer who are considering adjuvant or salvage radiotherapy after radical prostatectomy. Decisional effectiveness improves for both patients and providers with use of the Decipher test.